Effect of additional speed endurance training on performance and muscle adaptations - Gunnarsson, T. P.; Christensen, P. M.; Holse, K.; Christiansen, D.; Bangsbo, J. (Medicine & Science in Sports & Exercise, 2012)
Purpose: The present study examined the effect of additional speed endurance training (SET) during the season on muscle adaptations and performance of trained soccer players.